Remote focal scanning optical projection tomography with an electrically tunable lens - Chen,L; Kumar,S; Kelly,D; Andrews,N; Dallman,MJ; French,PMW; McGinty,J (Biomedical Optics Express, 2014)
We describe a remote focal scanning technique for optical projection tomography (OPT) implemented with an electrically tunable lens (ETL) that removes the need to scan the specimen or objective lens. Using a 4× objective lens the average spatial resolution is improved by ∼46% and the light collection efficiency by a factor of ∼6.76, thereby enabling increased acquisition speed and reduced light dose. This convenient implementation is particularly appropriate for lower magnifications and larger sample diameters where axial objective scanning would encounter problems with speed and stability.